2011
DOI: 10.1111/j.1444-0938.2010.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Corneal volume measures for monitoring contact lens induced corneal swelling: a pilot study

Abstract: Background:  This study investigated the use of corneal volume to monitor the corneal swelling response induced by wearing high plus power contact lenses. Methods:  Twelve young non‐contact lens wearers were recruited with one eye fitted with a soft contact lens (Polymacon material, 38.6 per cent water, Dk of 9 and 0.27 mm centre thickness) and the fellow eye served as control. The treated eye was patched for two hours leaving the control eye uncovered. Central corneal thickness (CCT) was measured with non‐con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Further studies are needed to determine the repeatability of endothelial cell density in Fuchs dystrophy, and to determine the relationship between endothelial cell density and the CPTR. Corneal volume is another parameter that been used to measure changes in corneal edema, 26,27 but an isolated measurement of corneal volume has the same limitations as an isolated measurement of CCT.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to determine the repeatability of endothelial cell density in Fuchs dystrophy, and to determine the relationship between endothelial cell density and the CPTR. Corneal volume is another parameter that been used to measure changes in corneal edema, 26,27 but an isolated measurement of corneal volume has the same limitations as an isolated measurement of CCT.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the Pentacam has excellent repeatability and reliability for measurements of both cornea (thickness, curvature, aberration and volume) and anterior chamber (depth and volume). In our study, the following cornea and anterior chamber parameters were evaluated with the Scheimpflug system: corneal curvature (front and back surface) maps, corneal volumes (the volume of cornea is calculated with corneal pachymetry software to evaluate the entire cornea in different rings around the apex: 3, 5, 7 or 10 mm), and aberrations (3rd‐, 4th‐ and higher order aberrations [HOAs]) of the anterior, posterior and total cornea.…”
Section: Methodsmentioning
confidence: 99%
“…Central corneal thickness (CCT) is used to screen candidates for refractive surgery, in order to reduce the risk of postoperative ectasia [6]. CCT readings are also crucial for the detection of contact lens-induced edema and diagnosis of corneal diseases, such as keratoconus and glaucoma [7][8][9].…”
Section: Introductionmentioning
confidence: 99%